Pengabdian kepada Masyarakat Berbasis Pondok Pesantren oleh Mahasiswa KKN STIBA Makassar di Kabupaten Jeneponto - Ihwan Wahid Minu; Kasman Bakry; Abdullah Nazhim Hamid (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Pondok Pesantren (Boarding Schools) is one of the educational services that are quite influential in the development of Muslim communities in Indonesia, including in the Region of South Sulawesi. One of the Boarding Schools located in Jeneponto Regency, South Sulawesi, is Pondok Pesantren Ulul Albab. Pondok Pesantren Ulul Albab focuses on the construction of memorization and teaching of the Qur'an. In addition, this boarding schools also continues to carry out formal learning in the classroom. therefore, Pondok Pesantren Ulul Albab became one of the destinations 4th KKN STIBA Makassar IV. The purpose of this Field Work Lecture (KKN) STIBA Makassar is to realize community service which is a pillar of the tri dharma of higher education in Indonesia. The method of community service implementation in Pondok Pesantren Ulul Albab begins with mapping the problems and needs of boarding schools by using instruments made simply by SOAR analysis. After that, mapping the work program that suits the needs of boarding schools. The program of activities carried out by students of STIBA Makassar is Qur'an and tahsin education, classroom learning, Friday sermons, lecture training, and devotional work. The results of the KKN program can be seen from enthusiastic students and teachers who are getting better at learning and teaching the Qur'an. It also provides a new learning experience for teachers and students.